2014
DOI: 10.1017/s095026881400123x
|View full text |Cite
|
Sign up to set email alerts
|

The association between campylobacteriosis, agriculture and drinking water: a case-case study in a region of British Columbia, Canada, 2005–2009

Abstract: We studied the association between drinking water, agriculture and sporadic human campylobacteriosis in one region of British Columbia (BC), Canada. We compared 2992 cases of campylobacteriosis to 4816 cases of other reportable enteric diseases in 2005-2009 using multivariate regression. Cases were geocoded and assigned drinking water source, rural/urban environment and socioeconomic status (SES) according to the location of their residence using geographical information systems analysis methods. The odds of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 37 publications
1
13
0
1
Order By: Relevance
“…The authors hypothesized that unpasteurized milk consumption may explain this attribution to cattle as raw milk and unpasteurized dairy products have been identified as the cause of several campylobacteriosis outbreaks (for example [43] or [44] and as a risk factor for sporadic infection [2]. Another hypothesis is the local contamination of water sources and wells in rural area by cattle manure whereby people may be contaminated locally [4548], in contrast to a wider spread of Campylobacter through the watershed that our water samples would have detected. These results should encourage public health authorities, food safety and water quality stakeholders to target the cattle farms for the prevention of Campylobacter transmission to humans through contact with cattle, consumption of raw milk or well water contaminated or not adequately treated, in addition to continue their efforts to reduce Campylobacter contamination along the poultry supply chain.…”
Section: Discussionmentioning
confidence: 99%
“…The authors hypothesized that unpasteurized milk consumption may explain this attribution to cattle as raw milk and unpasteurized dairy products have been identified as the cause of several campylobacteriosis outbreaks (for example [43] or [44] and as a risk factor for sporadic infection [2]. Another hypothesis is the local contamination of water sources and wells in rural area by cattle manure whereby people may be contaminated locally [4548], in contrast to a wider spread of Campylobacter through the watershed that our water samples would have detected. These results should encourage public health authorities, food safety and water quality stakeholders to target the cattle farms for the prevention of Campylobacter transmission to humans through contact with cattle, consumption of raw milk or well water contaminated or not adequately treated, in addition to continue their efforts to reduce Campylobacter contamination along the poultry supply chain.…”
Section: Discussionmentioning
confidence: 99%
“…In Poland, Popowski and colleagues detected C. jejuni, C. coli, or C. lari in 70% of water samples from rivers or lakes in the Warsaw region (374), supporting a role for contaminated water in the direct transmission of Campylobacter species to humans. Individuals who utilize private wells rather than municipal surface water systems as a drinking water source are at a higher risk of developing campylobacteriosis than other reportable enteric diseases (375).…”
Section: Watermentioning
confidence: 99%
“…Galanis et al (2014) examined the association between drinking water, agriculture, and 2992 cases of sporadic human campylobacteriosis in 2005-2009 in one region of British Columbia, Canada, and found that the odds of campylobacteriosis compared with 4816 other enteric disease controls were higher for individuals serviced by private wells than by municipal surface water systems and that the risk of campylobacteriosis compared with other enteric diseases seems to be mediated by vulnerable drinking water sources and rural factors. These studies indicate that Campylobacter outbreaks in Canada have been associated with inadequate treatment of small water systems.…”
Section: Campylobacters In the Environment Including Watermentioning
confidence: 99%